2011
DOI: 10.1590/s0102-695x2011005000030
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and effect of an essential oil of Salix aegyptiaca L., Salicaceae, (musk willow) in hypercholesterolemic rabbit model

Abstract: Abstract:The essential oils (EO) of Salix aegyptiaca L., Salicaceae (SA), leaves were extracted using the hydrodistillation method and their chemical composition was further determined by GC-MS. 1,4-Dimethoxybenzene was the main isolated compound. Other major isolated constitutes were phenylethyl alcohol, carvone, citronellol, methyleugenol, eugenol, n-tetradecane and 4´-methoxyacetophenone. Twenty rabbits were equally divided into four groups: Normal control (NC) which fed a standard diet and three cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In Iranian traditional medicine, S. aegyptiaca has been employed as laxative, cardioprotective, sedative, hypnotic, somnolent, aphrodisiac, orexigenic, carminative, gastroprotectant, anthelmintic, and vermifuge (Karimi et al. ). A number of chemical constituents such as flavonoids and volatile substances have been isolated from different parts of the plant (Enayat and Banerjee ; Karimi et al.…”
Section: Introductionmentioning
confidence: 99%
“…In Iranian traditional medicine, S. aegyptiaca has been employed as laxative, cardioprotective, sedative, hypnotic, somnolent, aphrodisiac, orexigenic, carminative, gastroprotectant, anthelmintic, and vermifuge (Karimi et al. ). A number of chemical constituents such as flavonoids and volatile substances have been isolated from different parts of the plant (Enayat and Banerjee ; Karimi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits also have significant differences in their lipid metabolism from humans, which can result in their development of "cholesterol storage syndrome" while on high-cholesterol diets (0.5-3%), with cholesterol deposited in their liver, adrenal cortex, and reticuloendothelial and genitourinary systems [108]. We found that a high-cholesterol diet contained in 0.47% cholesterol would be tolerable for adult male rabbits for 4 weeks but our high-cholesterol diet was mildly atherogenic [94,111]. The atherosclerotic lesions of rabbits do not completely resemble those in humans [108] and the formed lesions are more fatty and macrophage rich than human [112].…”
Section: The Rabbit Modelsmentioning
confidence: 74%
“…In contrast to hamsters they do not possess a fore-stomach fermentation which modifies dietary macronutrients before reaching the small intestine [89]. Guinea pigs are not only superior models for studying the mechanisms by which statins [90], cholestyramine [91], apical sodium bile acid transport inhibitors [92] and microsomal transfer protein inhibitors [93] lower plasma LDL-C but also are selected to investigate the mechanisms by which certain drugs or toxins affect lipidlipoprotein metabolism (e.g., [94]). Guinea pigs respond to dietary fat saturation, dietary cholesterol and dietary fiber by alterations in LDL-C (see review [87]).…”
Section: The Guinea Pig Modelsmentioning
confidence: 99%
“…In Iran it is found in some province. The flowers are important parts of the plant for therapeutic purposes that separate to male flower and female flower and each plant only has one sex [51]. In Iranian traditional medicine the male inflorescences distillate has been used to treat depression, anemia, vertigo, as well as cardiovascular problems.…”
Section: Salix Aegyptiacamentioning
confidence: 99%